Integration of the 2030 Agenda in Argentine Higher Education: Strategies, gaps, and institutional performance - Arias-Valle, María Belén (2026)
This study examines the commitment of Argentine universities to the Sustainable Development Goals (SDGs) through an analysis of their performance in the Times Higher Education Impact Rankings (THE-IR). Employing a quantitative, descriptive, and geographically oriented approach, the research compares public and private institutions, identifying priorities and gaps in sustainability integration. The findings reveal a strong institutional emphasis on SDG 4 (Quality Education), SDG 5 (Gender Equality), and SDG 17 (Partnerships for the Goals), while environmental and technology-related goals exhibit comparatively low levels of integration. Differences are observed according to institutional type and geographic location, reflecting underlying structural inequalities within the higher education system. The study concludes that ranking performance is influenced not only by sustainability initiatives but also by reporting capacity and thematic specialization. Although progress is evident, more comprehensive institutional strategies and more robust impact measurement mechanisms are required to advance sustainability in Argentine higher education.